PENGARUH PMRI DENGAN KONTEKS MAKANAN KHAS PALEMBANG TERHADAP PEMAHAMAN KONSEP PENGUKURAN PADA KELAS III SD XAVERIUS 4 PALEMBANG - Fransiska Amanda Wulandari; B. A. Indriasari; Anastasia Sri Sukistini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of applying the principles of Indonesian Realistic Mathematics Education (PMRI) by utilizing the context of traditional Palembang food in Deep Learning-based instruction on students’ conceptual understanding of length and weight measurement in third-grade elementary school students. This research employed a quantitative method with a true experimental design. The research sample consisted of two classes: an experimental class that applied PMRI principles through the use of traditional Palembang food contexts, namely pempek lenjer and pempek adaan, in Deep Learning-based instruction, and a control class that used conventional learning. Data were collected through an individual test to measure students’ conceptual understanding. The obtained data were analyzed using the Mann–Whitney test after fulfilling the prerequisite tests. The results showed that there was a significant difference in students’ conceptual understanding between the experimental and control classes in the topic of length and weight measurement, with a significance value of < 0.05. The mean rank score of the experimental class was higher than that of the control class. Therefore, the application of PMRI principles utilizing the context of traditional Palembang food in Deep Learning-based instruction was proven to have a positive effect on improving students’ conceptual understanding of measurement in a more meaningful and contextual way.